To Investigate the Relative Effects of Various Political Media on Political Engagement and Attitude (Journal of Advances and Scholarly Researches in Allied Education, 2023)
Electronic mail, social media, file sharing, online banking, e-commerce, travel, online food ordering, corporate advertising, navigation, real-time news, and many more applications are woven into every facet of everyday life. Some examples of platforms that facilitate transactions between buyers and sellers are WhatsApp, Instagram, YouTube, and Facebook groups. Instagram and Facebook are also utilized as platforms for company promotion and marketplaces. The purpose of this paper is to provide some explanation for the correlation between political involvement as expressed on social media and real participation in political processes. An online survey is sent over WhatsApp, Facebook, and email to individuals of all ages and backgrounds.